Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation

Hydrogenolysis of sorbitol over Ni, Pt and Ru supported on SBA-15 - Banu, M.; Sankaranarayanan, T. M.; Venuvanalingam, P.; Magesh, G.; Sivasanker, S. (Indian Journal of Chemistry. Section A: Inorganic, Physical, Theoretical & Analytical Chemistry, 2017)
Hydrogenolysis of sorbitol (15% aqueous solution) has been carried out in a batch reactor over Ni (6 wt%), Pt (1 wt%) and Ru (1 wt%) supported on SBA-15 and carbon coated SBA-15 (SBA-15(C)). For comparison, the three metals have also been supported on activated carbon (AC). The catalysts are characterized by XRD, N-2 and H-2 adsorption measurements. Addition of Ca(OH)(2) to the reaction mixture increases conversion and selectivity for the dihydroxy compounds, 1,2-propanediol (PD) and ethylene glycol (EG). Based on yield of dihydric alcohols (PD+EG), the performance of the catalysts at 220 degrees C and 60 bar in the presence of Ca(OH)(2) is in the order: Ru-AC similar to Ru-SBA-15(C) > Ru-SBA-15 similar to Ni-SBA-15, the yields being 40, 39, 31 and 29 wt%, respectively.